The distinction between the subjectivist and objectivist formulation of possession and what is the solution adopted by the civil code Portuguese - Carrera, Murillo Magalhães (Revista Jurídica Portucalense, 2020)
Under the terms of Article 1251 of the Civil Code possession is the power that manifests itself when someone acts in a manner corresponding to the exercise of the right to property or another real right. In the traditional understanding of Portuguese doctrine, the interpretation of the aforementioned precept must be combined with paragraph a) of article 1255 of the Civil Code, meaning that the concept of possession in addition to presupposing the exercise of de detention over certain thing, also foresees that the owner acts with the intention of acting as holder. To this extent, the overwhelming majority of Portuguese doctrine and jurisprudence understand that the Portuguese legislator enshrined in the Civil Code a subjectivist theory of possession. In light of the above, this report aims to counter the aforementioned perspective and address a different view of the institute.